Analisis Sistem Akuntansi pada Operasional Penerimaan Kas di Yayasan XYZ - Reny Lia Riantika; Farhan Kamil Rabbani (Rahmatan Lil 'Alamin Journal of Community Services, 2022)
This activity aims to find out how the cash receipts accounting system is implemented at the XYZ Foundation and find out what are the obstacles that occur in the system. By knowing how the accounting system works and the constraints experienced, this activity analyzes and helps provide recommendations regarding these problems as a form of community service by conducting interviews with the finance department and accounting staff. The data obtained from the interviews were then analyzed using a qualitative descriptive method with a qualitative approach. After the process of analyzing the related data, it was found that the accounting system that applies at the XYZ Foundation with the help of an accounting application, namely Zahir Offline, still found some weaknesses. The main weakness is that the whole process is still done manually and is only done by one person, which is very vulnerable to human error. The role of the accounting system is crucial in supporting company performance, so it is important for business people to ensure that the accounting system used is in accordance with the business being undertaken and minimize gaps in it.